Polypharmacy in elective lumbar spinal surgery for degenerative conditions with 24-month follow-up - Nicholas Dietz; Chitra Kumar; Aladine A. Elsamadicy; Martin F. Bjurström; Katrina Wong; Alysha Jamieson; Mayur Sharma; Dengzhi Wang; Beatrice Ugiliweneza; Doniel Drazin; Maxwell Boakye (Scientific Reports)
Abstract We sought to identify long-term associations of medical complications and healthcare utilization related to polypharmacy following spinal surgery for degenerative lumbar pathology. The IBM MarketScan dataset was used to select patients who underwent spinal surgery for degenerative lumbar pathology with 2-year follow-up. Regression analysis compared two matched cohorts: those with and without polypharmacy. Of 118,434 surgical patients, 68.1% met criteria for polypharmacy. In the first 30 days after discharge, surgical site infection was observed in 6% of those with polypharmacy and 4% of those without polypharmacy (p < 0.0001) and at least one complication was observed in 24% for the polypharmacy group and 17% for the non-polypharmacy group (p < 0.0001). At 24 months, patients with polypharmacy were more likely to be diagnosed with pneumonia (48% vs. 37%), urinary tract infection (26% vs. 19%), and surgical site infection (12% vs. 7%), (p < 0.0001). The most prescribed medication was hydrocodone (60% of patients) and more than 95% received opioids. Two years postoperatively, the polypharmacy group had tripled overall healthcare utilization payments ($30,288 vs. $9514), (p < 0.0001). Patients taking 5 or more medications concurrently after spinal surgery for degenerative lumbar conditions were more likely to develop medical complications, higher costs, and return to the emergency department.